2018
DOI: 10.1016/j.eururo.2018.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Burden of Metastatic Castrate Naive Prostate Cancer Patients, to Identify Men More Likely to Benefit from Early Docetaxel: Further Analyses of CHAARTED and GETUG-AFU15 Studies

Abstract: Patients with a higher burden of metastatic prostate cancer starting androgen deprivation therapy (ADT) have a poorer prognosis and are more likely to benefit from early docetaxel. Low-volume patients have longer overall survival with ADT alone, and the toxicity of docetaxel may outweigh its benefits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
130
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 208 publications
(139 citation statements)
references
References 26 publications
3
130
0
6
Order By: Relevance
“…The present study showed that the CHAARTED and LATITUDE risk criteria could apply to Japanese patients. Furthermore, prognoses in clinical trials including GETUG‐AFU 15, CHAARTED and LATITUDE were apparently worse than those in real‐world studies from the USA, Western Europe and Japan; whereas prognoses in the real‐world studies seem to be similar, with small differences (Table ). In particular, the difference in OS between clinical trials and the present study would be greater when age was adjusted, which might be due to differences in race and medical care for castration‐resistant prostate cancer.…”
mentioning
confidence: 97%
“…The present study showed that the CHAARTED and LATITUDE risk criteria could apply to Japanese patients. Furthermore, prognoses in clinical trials including GETUG‐AFU 15, CHAARTED and LATITUDE were apparently worse than those in real‐world studies from the USA, Western Europe and Japan; whereas prognoses in the real‐world studies seem to be similar, with small differences (Table ). In particular, the difference in OS between clinical trials and the present study would be greater when age was adjusted, which might be due to differences in race and medical care for castration‐resistant prostate cancer.…”
mentioning
confidence: 97%
“…When considering optimal systemic therapy for low‐volume and high‐volume disease in mCSPC, the panel reached a consensus that in low‐volume mCSPC, there is strong evidence that ADT + docetaxel does not provide an OS benefit beyond ADT alone; thus, ADT + AA is favored in the low‐volume setting. However, there was unanimous consensus that in high‐volume mCSPC, there is strong evidence of OS benefit for ADT + docetaxel 70,71 . Thus, both ADT + AA or ADT + docetaxel are equally preferred treatment options in the high‐volume setting (Table 4).…”
Section: Resultsmentioning
confidence: 99%
“…However, there was unanimous consensus that in high-volume mCSPC, there is strong evidence of OS benefit for ADT + docetaxel. 70,71 Thus, both ADT + AA or ADT + docetaxel are equally preferred treatment options in the highvolume setting (Table 4). These recommendations are in line with the NCCN guideline.…”
Section: The Role Of Adt In Salvage Therapymentioning
confidence: 99%
“…In contrast, neutropenia, febrile neutropenia, fatigue, and sensory neuropathies were the most commonly seen grade 3/4 toxicities in patients receiving docetaxel. New evidence has shown that patients with low-volume metastases did not benefit from ADT plus early docetaxel [48]. Therefore, further investigations should be aimed at evaluating whether docetaxel or abiraterone added to ADT can provide survival benefits for patients with major cardiovascular comorbidities.…”
Section: Discussionmentioning
confidence: 99%